A price premium for the farmer‐owned label? A choice experiment with milk consumers in the Netherlands. Issue 4 (18th March 2021) - Grashuis, Jasper
Abstract: Organized milk producers may use marketing mechanisms in response to price and policy variability. While adopted by numerous milk producer co‐operatives across the world, the farmer‐owned label is not yet used in the Dutch consumer marketplace. We estimate the viability of the farmer‐owned label in the Netherlands with a branded choice experiment. We observe a significant and positive willingness‐to‐pay for the farmer‐owned label, but only given the disclosure of additional information in terms of profit allocation to farmers as opposed to investors. Further variation in the willingness‐to‐pay across attributes is indicative of its complex position in the crowded landscape of marketing mechanisms. [EconLit Citations: C25, D83, D91, Q13].